2019
DOI: 10.1158/1078-0432.ccr-19-0075
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Lymph Node Metastasis in Breast Cancer by Gene Expression and Clinicopathological Models: Development and Validation within a Population-Based Cohort

Abstract: Purpose: More than 70% of patients with breast cancer present with node-negative disease, yet all undergo surgical axillary staging. We aimed to define predictors of nodal metastasis using clinicopathological characteristics (CLINICAL), gene expression data (GEX), and mixed features (MIXED) and to identify patients at low risk of metastasis who might be spared sentinel lymph node biopsy (SLNB).Experimental Design: Breast tumors (n ¼ 3,023) from the population-based Sweden Cancerome Analysis Network-Breast init… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 54 publications
1
30
3
Order By: Relevance
“…Here, the best-performing DL-CNB model yielded satisfactory predictions with an AUC of 0.816, a SENS of 81.0%, and a SPEC of 70.9% on the test set, which had superior predictive capability compared with clinical data alone. Furthermore, unlike other combined models incorporating clinical data (7,9), the DL-CNB+C model slightly improved the ACC to 0.831, which showed that our results were mainly derived from the contribution of DL-CNB model. In addition, during the subgroup analysis stratified by patient's age, our DL-CNB+C model achieved an AUC of 0.918 for patients younger than 50 years, indicating that age was the critical factor in predicting ALN status.…”
Section: Discussioncontrasting
confidence: 58%
“…Here, the best-performing DL-CNB model yielded satisfactory predictions with an AUC of 0.816, a SENS of 81.0%, and a SPEC of 70.9% on the test set, which had superior predictive capability compared with clinical data alone. Furthermore, unlike other combined models incorporating clinical data (7,9), the DL-CNB+C model slightly improved the ACC to 0.831, which showed that our results were mainly derived from the contribution of DL-CNB model. In addition, during the subgroup analysis stratified by patient's age, our DL-CNB+C model achieved an AUC of 0.918 for patients younger than 50 years, indicating that age was the critical factor in predicting ALN status.…”
Section: Discussioncontrasting
confidence: 58%
“…A number of predictive models have been made based on ML algorithms. Several studies have reported effective ML-based models for the prediction of LNM in other carcinomas, such as breast cancer (10,11). It was reported that radiomics could be used to predict LNM by analyzing radiological images in NSCLC (12).…”
Section: Introductionmentioning
confidence: 99%
“…The highest true validation value (AUC: 0.75) suggests that the SUS nomogram does not perfectly predict a disease-free axilla, which highlights the complexity of lymphatic spread. Although more complex prediction models may have certain advantages for estimating nodal involvement 44 , 45 , the SUS nomogram is a readily available and user-friendly predictive tool in clinical settings. Studies based on retrospective registry data may be considered unreliable, given the risks of incomplete or improperly recorded data.…”
Section: Discussionmentioning
confidence: 99%